Frequent failure of water supply in army camps in Ipoh - Kumaran Kumaraweh, 1974-, author 611419; Norhazilan Md. Noor, supervisor 338581; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Sarjana Kejuruteraan (Awam)